Performance investigation of a gasifier and gas engine system operated on municipal solid waste briquettes - Homdoung, Nigran; Dussadee, Nattawud; Sasujit, Kittikorn; Kiatsiriroat, Tanongkiat; Tippayawong, Nakorn (International Journal of Renewable Energy Development, 2019)
Municipal solid waste (MSW) and charcoal can be used as a substitute fuel in a gas engine. In this work, performance of a downdraft gasifier and gas engine system operated on MSW briquette fuel was investigated. Experimental test was carried out on a 62 kW, four-cylinder, naturally aspirated engine coupled to a 20 kW dynamometer. The downdraft gasifier was used to generate producer gas from MSW briquettes and charcoal. The engine load was varied between 1.5-9.0 kW. Biomass consumption, producer gas production, cold gas efficiency, thermal efficiency of the gas engine, carbon monoxide (CO), hydrocarbon (HC) emissions and exhaust temperature were evaluated. The MSW briquette fuelled operation was compared against that with charcoal. It was found that, the use of MSW briquette led to lowering performance of the downdraft gasifier and gas engine system, in comparison with the use of charcoal. Maximum cold gas and thermal efficiencies obtained were 64.6% and 16% at 4.5 kW and 9 kW loading, respectively. The CO and HC emissions of the gas engine operated on MSW briquettes were higher than that on charcoal, while the exhaust temperatures were similar. Â©2019. CBIORE-IJRED. All rights reserved